2000
DOI: 10.1007/s11738-000-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soluble carbohydrate level in Hordeum vulgare (L.) and Festuca pratensis (Huds.) calli treated with metabolites of Bipolaris sorokiniana (Sacc.) Shoem

Abstract: Changes in soluble carbohydrate level in Hordeum vulgare (L.) and Festuca pratensis (Huds.) calli treated with metabolites of Bipolaris sorokiniana (Sacc.) Shoem. AbstractCalli of spring barley (Hordeum vulgate L.) and meadow fescue (Festuca pratensis Huds.) were treated with metabolites of Bipolaris sorokiniana and then the level of soluble carbohydrates was estimated. Fructose and glucose occurred in the greatest amount in non-treated calli (control). Control tissue of both species responded to a change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…(1998) found that tomato, maize and cotton plants characterized by low sugar concentration were more sensitive to pathogen attack than plants richer in sugars. Significant changes in soluble carbohydrate content in barley and fescue tissue during pathogenesis caused by B. sorokiniana were shown previously (Płażek and Niemczyk 2000). Tronsmo (1986) showed a decrease in the Ψ w of leaf cells of hardened grasses Phleum and Phalaris with simultaneous weaker development of Microdochium nivale on their leaves.…”
Section: Discussionsupporting
confidence: 67%
“…(1998) found that tomato, maize and cotton plants characterized by low sugar concentration were more sensitive to pathogen attack than plants richer in sugars. Significant changes in soluble carbohydrate content in barley and fescue tissue during pathogenesis caused by B. sorokiniana were shown previously (Płażek and Niemczyk 2000). Tronsmo (1986) showed a decrease in the Ψ w of leaf cells of hardened grasses Phleum and Phalaris with simultaneous weaker development of Microdochium nivale on their leaves.…”
Section: Discussionsupporting
confidence: 67%
“…is study also demonstrated a differential response of calli to metabolites compared to the response of leaves to spore inoculation with this fungus. Płażek and Niemczyk (2000) conducted a study to compare the response of callus tissue of meadow fescue, which is more resistant to B. sorokiniana, and barley, which is markedly more sensitive to this pathogen. ese studies demonstrated that the response to this stress occurs in two phases.…”
Section: Investigation Of Plant Resistance To Pathogensmentioning
confidence: 99%